Modified glass sheet as well as preparation method and application thereof
By controlling the content of magnesium on the tin surface in the float glass than the content of the air surface, the problem that float glass is prone to warping after chemical strengthening is solved, and the low warpage and high stress strength of the chemically strengthened glass are achieved. Cover glass suitable for electronic equipment.
Patent Information
- Application Number
- CN202411461336.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-14
AI Technical Summary
Floating glass is prone to warping after chemical reinforcement, affecting its performance when used as cover glass.
By controlling the magnesium content of the tin surface higher than the magnesium content of the air surface, the ion exchange rate and depth of the tin surface during the chemical strengthening process are improved, and the ion exchange rate of the tin surface and the air surface during the chemical strengthening process are reduced. Differences in degrees.
It effectively reduces the warpage value of chemically strengthened glass, makes it have a low warpage rate, improves the stress depth and stress strength, and is suitable for cover glass for electronic equipment.
Smart Images

Figure BDA0005091951290000111 
Figure BDA0005091951290000121 
Figure BDA0005091951290000122
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of electronic glass, and in particular relates to a modified glass sheet and a preparation method and application thereof. Background Art
[0002] Glass cover is an important component of electronic devices, often used as a touch display unit, to protect precision electronic components such as touch sensors and display panels. With the development of electronic devices, such as mobile displays such as mobile phones and tablets, the requirements for cover glass are getting higher and higher. For example, the cover glass is not only required to be thin, but also to have advantages such as high strength, scratch resistance, and good impact resistance.
[0003] At present, a certain proportion of cover glass on the market is produced by float process. The glass produced by float process has good flatness and strong optical properties, but the glass produced by float process usually needs further strengthening to improve the strength, scratch resistance and impact resistance of the glass.
[0004] In the prior art, the strengthening method of float glass includes chemical strengthening method. However, the glass surface produced by float process will have tin surface and air surface, and the glass composition of tin surface and air surface is different. For example, the tin surface has tin infiltration due to contact with tin liquid, and the presence of Sn ions will reduce the ion exchange rate during chemical strengthening. This leads to different ion exchange rates between tin surface and air surface during chemical strengthening of float glass, which in turn leads to inconsistent surface compressive stress (CS) and ion exchange depth (DOL) on both sides of strengthened glass, resulting in warping of chemically strengthened glass. This warping seriously affects the performance of these strengthened glasses when used as cover glass. Summary of the invention
[0005] The purpose of the present application is to provide a modified glass sheet and a preparation method thereof, so as to solve the technical problem in the prior art that float glass is prone to warping after chemical strengthening.
[0006] The embodiments of the present application also provide a chemically strengthened glass and a preparation method thereof, a cover glass and an electronic device.
[0007] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0008] In a first aspect, an embodiment of the present application provides a modified glass substrate. The modified glass substrate of the embodiment of the present application comprises a tin surface and an air surface, wherein the magnesium content in the tin surface is higher than the magnesium content in the air surface.
[0009] The modified glass sheet of the embodiment of the present application controls the magnesium content of the tin surface to be higher than the magnesium content of the air surface, thereby improving the ion exchange rate and ion exchange depth of the tin surface during the chemical strengthening treatment, and reducing the difference in ion exchange rate and ion exchange degree between the tin surface and the air surface during the chemical strengthening treatment, thereby effectively reducing the warpage value of the modified glass sheet of the embodiment of the present application after chemical strengthening, so that the chemically strengthened glass obtained from the modified glass sheet of the embodiment of the present application after chemical strengthening treatment has a low warpage rate.
[0010] In a second aspect, the present application provides a method for preparing the modified glass sheet mentioned above. The method for preparing the modified glass sheet in the present application comprises the following steps:
[0011] The tin surface of the float glass original sheet is placed in a magnesium-containing molten salt for a first ion exchange treatment to obtain a modified glass original sheet.
[0012] In the process of the first ion exchange treatment, the tin ions contained in the tin surface of the float glass original sheet are partially or completely replaced by magnesium ions in the method for preparing the modified glass original sheet in the embodiment of the present application, thereby effectively increasing the magnesium ion content contained in the tin surface of the float glass original sheet, and further making the magnesium ion content of the tin surface higher than that of the air surface. This effectively reduces the difference in ion exchange rate between the tin surface and the air surface of the prepared modified glass original sheet during the chemical strengthening treatment, as well as the difference in ion exchange degree, thereby effectively reducing the warpage value of the chemically strengthened glass. In addition, the method for preparing the modified glass original sheet in the embodiment of the present application has fewer process steps, and the process conditions are easy to control, which is suitable for large-scale industrial production.
[0013] In a third aspect, the present invention provides a chemically strengthened glass. The chemically strengthened glass of the present invention is prepared by chemically strengthening the modified glass sheet described above, or by chemically strengthening the modified glass sheet prepared by the modified glass sheet preparation method described above.
[0014] Since the magnesium content of the tin surface of the modified glass original sheet is high, the stress intensity of the tin surface after chemical strengthening treatment is large, and the stress depth is large. In addition, since the difference in ion exchange rate and ion exchange degree of the modified glass original sheet during the chemical strengthening treatment is small, the warpage value of the chemically strengthened glass in the embodiment of the present application is low.
[0015] In a fourth aspect, the present invention provides a method for preparing the chemically strengthened glass mentioned above. The method for preparing the chemically strengthened glass in the present invention comprises the following steps:
[0016] The modified glass sheet is subjected to chemical strengthening treatment to obtain chemically strengthened glass.
[0017] Since the tin surface of the modified glass original sheet in the above text has a fast ion exchange rate and a high ion exchange degree during the chemical strengthening process, the chemically strengthened glass preparation method of the present application embodiment can produce chemically strengthened glass with a large stress depth and a high stress intensity. In addition, since the difference in ion exchange rate and ion exchange degree between the tin surface and the air surface of the modified glass original sheet in the above text during the chemical strengthening process is small, the chemically strengthened glass produced by the chemically strengthened glass preparation method of the present application embodiment has a low warpage value.
[0018] In a fifth aspect, the embodiments of the present application provide a cover glass. The cover glass of the embodiments of the present application includes the chemically strengthened glass mentioned above, or the chemically strengthened glass prepared by the method for preparing chemically strengthened glass mentioned above.
[0019] The chemically strengthened glass mentioned above has a low warping value, high stress intensity, and great stress depth, so that the cover glass of the embodiment of the present application also has the characteristics of low warping and high strength, thereby enabling the cover glass of the embodiment of the present application to fit better and more closely with other components of the electronic device, and to improve the yield rate during the production of the electronic device, while also reducing the production cost, improving the response speed and display quality of the touch screen, and enhancing the user experience.
[0020] In a sixth aspect, an embodiment of the present application provides an electronic device. The electronic device of the embodiment of the present application includes the cover glass described above.
[0021] Since the cover glass has a low warpage value and high strength as described above, the touch screen of the electronic device in the embodiment of the present application has a fast response speed, high display quality, and good user experience. DETAILED DESCRIPTION
[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0023] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0024] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.
[0025] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0026] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0027] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.
[0028] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0029] In order to solve the technical problem in the prior art that float glass is prone to warping after chemical strengthening, the present application proposes the following technical solution.
[0030] In a first aspect, an embodiment of the present application provides a modified glass substrate. The modified glass substrate of the embodiment of the present application comprises a tin surface and an air surface, wherein the content of magnesium in the tin surface is greater than the content of magnesium in the air surface.
[0031] The tin side of the modified glass sheet in the embodiment of the present application is the side of the glass that is in direct contact with the tin liquid when the glass is prepared by the float process. The air side can also be called the non-tin side, which is the side of the glass that is not in direct contact with the tin liquid when the glass is prepared by the float process. It should be noted that the air side is not limited to being in contact with only the air, but can also be the side of the glass that is in contact with other gas media such as nitrogen, helium, argon, etc. when the glass is prepared by the float process, without specific limitation.
[0032] Due to the influence of tin infiltration on the tin surface of float glass, the ion exchange rate of the tin surface during chemical strengthening of float glass is slower and the depth of ion exchange is shallower. Compared with the tin surface, the ion exchange rate of the air surface is faster and the depth of ion exchange is greater, which leads to a difference in the degree of ion exchange between the tin surface and the air surface of float glass.
[0033] The modified glass original sheet of the embodiment of the present application controls the magnesium content of the tin surface to be higher than the magnesium content of the air surface, so that the magnesium ions in the tin surface can promote the ion exchange of the tin surface of the modified glass original sheet during the chemical strengthening treatment of the modified glass original sheet. This improves the ion exchange rate and ion exchange depth of the tin surface, reduces the difference in the degree of ion exchange between the tin surface and the air surface of the modified glass original sheet during the chemical strengthening treatment, and thus reduces the warpage value of the chemically strengthened glass obtained, so that the chemically strengthened glass obtained after the modified glass original sheet of the embodiment of the present application undergoes chemical strengthening treatment has a low warpage rate.
[0034] In addition, since magnesium ions can promote ion exchange on the tin surface, controlling the magnesium content on the tin surface to be higher than the magnesium content on the air surface can further increase the stress depth of the tin surface after chemical strengthening, thereby further improving the stress depth and stress intensity of the modified glass sheet after chemical strengthening in the embodiment of the present application.
[0035] In some embodiments, the modified glass sheet may further contain sodium. When the modified glass sheet contains sodium, within the range of 15 μm or less depth between the tin surface and the air surface, the contents of sodium, magnesium and tin in the modified glass sheet satisfy ([MgO] 空气 +[Na2O] 空气 ):([MgO] 锡 +[Na2O] 锡 -[SnO2] 锡 )=1:(0.95~1.1), can be selected as, 1:(0.95~1.03), 1:0.98~1.03; or satisfy ([MgO] 空气 +[Na2O] 空气 ) / ([MgO] 锡 +[Na2O] 锡 -[SnO2] 锡)=0.95~1.1, which can be 0.95~1.03, 0.98~1.03. That is, in the modified glass sheet, within the range of 15μm depth between the tin surface and the air surface, the total mass fraction of magnesium oxide and sodium oxide in the air surface ([MgO] 空气 +[Na2O] 空气 ) and the difference between the total mass fraction of magnesium oxide and sodium oxide in the tin surface and the mass fraction of tin oxide ([MgO] 空气 +[Na2O] 空气 -[SnO2] 锡 ) can be 1:(0.95-1.1), optionally 0.95-1.03, 0.98-1.03. In the exemplary embodiment, within the range of 15 μm depth between the tin surface and the air surface, the ([MgO] 空气 +[Na2O] 空气 ):([MgO] 锡 +[Na2O] 锡 -[SnO2] 锡 ) can be 1:0.95, 1:0.96, 1:0.97, 1:0.98, 1:0.99, 1:1.00, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, etc., which are typical but non-limiting values, or any value between any two numerical values. Controlling the ([MgO] 空气 +[Na2O] 空气 ) / ([MgO] 锡 +[Na2O] 锡 -[SnO2] 锡 ) is within this range, the difference in ion exchange rate and degree of ion exchange between the tin surface and the air surface during the chemical strengthening process is further reduced, thereby further reducing the warpage value of the chemically strengthened glass obtained after the modified glass sheet of the embodiment of the present application is chemically strengthened.
[0036] In some embodiments, when the depth of the tin surface of the modified glass original sheet is in the range of ≤15 μm, the tin infiltration amount of the tin surface of the modified glass original sheet can be 0.15% to 0.35%, optionally 0.15% to 0.20%, 0.15% to 0.30%, 0.20% to 0.35%, 0.20% to 0.30%, 0.25% to 0.35%. In the exemplary embodiment, the tin penetration amount of the tin surface of the modified glass original sheet can be 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35% and other typical but non-limiting values, or any value within any two numerical ranges. Controlling the tin penetration amount of the tin surface within this range further reduces the influence of tin ions on the ion exchange rate during the chemical strengthening process of the tin surface, thereby further reducing the difference in ion exchange rate and exchange degree between the tin surface and the air surface during chemical strengthening, and reducing the warpage value of the modified glass original sheet after chemical strengthening of the embodiment of the present application.
[0037] In some embodiments, the thickness of the modified glass sheet can be 0.1-5 mm, and can be 0.1-1 mm, 0.1-2 mm, 0.1-3 mm, 0.5-1 mm, 0.5-2 mm, 0.5-4 mm. In the exemplary embodiment, the thickness of the modified glass sheet can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, etc., which are typical but non-limiting thicknesses, or any thickness between any two numerical ranges. Controlling the thickness of the modified glass sheet within this range further improves the strength of the chemically strengthened glass obtained, reduces the warpage value of the chemically strengthened glass, and further meets the market demand for thinner and thinner cover glass thickness.
[0038] In some embodiments, the modified glass original sheet of the embodiment of the present application may also contain calcium. In a further embodiment, when the modified glass original sheet of the embodiment of the present application contains calcium, the calcium content of the air side may be greater than the calcium content of the tin side. When the modified glass original sheet contains calcium ions, the presence of calcium ions will reduce the ion exchange rate of the modified glass original sheet during the chemical strengthening treatment process. Controlling the calcium content of the air side to be greater than the calcium content of the tin side can appropriately reduce the ion exchange rate of the air side of the modified glass original sheet during the chemical strengthening treatment process, thereby further reducing the difference in ion exchange rate and exchange degree between the tin side and the air side, and further reducing the warpage value of the chemically strengthened glass obtained by chemically strengthening the modified glass original sheet of the embodiment of the present application.
[0039] In a further embodiment, the difference between the calcium content of the air side and the calcium content of the tin side in the modified glass original sheet can be greater than 0 and less than or equal to 0.5%, and can be selected from 0.1% to 0.3%, 0.1% to 0.4%, 0.1% to 0.5%, 0.2% to 0.5%, and 0.3% to 0.5%. In the exemplary embodiment, the difference between the calcium content of the air side and the calcium content of the tin side can be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, and other typical but non-limiting values, or a value within any two numerical ranges. The difference between the calcium content of the air side and the calcium content of the tin side is controlled within this range, and the difference in the ion exchange rate and exchange degree between the tin side and the air side is further reduced, and the warpage value of the chemically strengthened glass obtained by chemically strengthening the modified glass original sheet of the embodiment of the present application is reduced.
[0040] In a second aspect, the present invention provides a method for preparing the modified glass sheet mentioned above. The method for preparing the modified glass sheet in the present invention comprises the following steps:
[0041] Step S10: placing the tin surface of the float glass original sheet in a magnesium-containing molten salt for a first ion exchange treatment to obtain a modified glass original sheet.
[0042] The modified glass original sheet preparation method of the embodiment of the present application places the tin surface of the float glass original sheet in a magnesium-containing molten salt for a first ion exchange treatment to obtain the modified glass original sheet mentioned above. During the first ion exchange treatment, the tin ions contained in the tin surface of the float glass original sheet are partially or completely replaced by magnesium ions, thereby effectively increasing the magnesium ion content contained in the tin surface of the float glass original sheet to obtain the tin surface mentioned above, and making the magnesium content of the tin surface higher than the magnesium content of the air surface. Since magnesium ions promote the ion exchange of the tin surface of the modified glass original sheet during the chemical strengthening treatment, the difference in the ion exchange rate and degree between the tin surface and the air surface of the modified glass original sheet is effectively reduced, and the warpage value of the obtained chemically strengthened glass is reduced. In addition, the modified glass original sheet preparation method of the embodiment of the present application has few process steps, and the process conditions are easy to control, which is suitable for large-scale industrial production.
[0043] In some embodiments, the temperature of the first ion exchange treatment can be 600-680°C, optionally 600-650°C, 630-680°C. In the exemplary embodiment, the temperature of the first ion exchange treatment can be 600°C, 605°C, 610°C, 615°C, 620°C, 625°C, 630°C, 635°C, 640°C, 645°C, 650°C, 655°C, 660°C, 665°C, 670°C, 675°C, 680°C, etc., which are typical but non-limiting temperatures, or any temperature between any two numerical ranges. Controlling the temperature of the first ion exchange treatment further promotes the full melting of the magnesium-containing molten salt; increases the exchange rate between tin ions and magnesium ions, further promotes the full ion exchange between tin ions and magnesium ions, and reduces the deformation of the glass.
[0044] In some embodiments, the time of the first ion exchange treatment can be 0.5 to 3 hours, and can be 0.5 to 2 hours, 0.5 to 1 hour, 1 to 3 hours, or 1 to 2 hours. In the exemplary embodiment, the time of the first ion exchange treatment can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, and other typical but non-limiting times, or any time between any two numerical ranges. Controlling the time of the first ion exchange treatment within this range further promotes the full ion exchange between magnesium ions and tin ions, effectively saves energy consumption, and further improves production efficiency.
[0045] In some embodiments, electric field assistance can be used to accelerate the ion exchange rate of magnesium ions and tin ions during the first ion exchange process, further promoting the ion exchange between magnesium ions and tin ions. In an exemplary embodiment, the electric field assistance can be performed in an interval manner, wherein the interval time can be 1 to 20 minutes; and the time of each electric field assistance can be 5 to 10 minutes.
[0046] In some embodiments, the magnesium-containing molten salt may include at least one of magnesium salts such as magnesium nitrate, magnesium carbonate, and magnesium chloride. In a further embodiment, the magnesium-containing molten salt may contain a magnesium salt with a mass fraction of 50% to 100%. In a demonstration example, the magnesium-containing molten salt may contain a magnesium nitrate with a mass fraction of 50% to 100%. The mass content of magnesium nitrate in the magnesium-containing molten salt may also be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc., which are typical but non-limiting content sizes, or any content size between any two numerical ranges.
[0047] In some embodiments, the magnesium-containing molten salt may also contain other non-magnesium salt components. In an exemplary embodiment, the magnesium-containing molten salt may also include at least one of sodium nitrate, sodium chloride, etc. In a further embodiment, when the magnesium-containing molten salt contains sodium nitrate, the mass content of sodium nitrate may be greater than 0 and less than or equal to 50%. In an exemplary embodiment, the content of sodium nitrate in the magnesium-containing molten salt may be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., which are typical but non-limiting values, or any value between any two numerical ranges.
[0048] The contents of components such as magnesium nitrate and sodium nitrate in the magnesium-containing molten salt are controlled within this range, so that the magnesium-containing molten salt has a higher magnesium ion content, and at the same time, the melting temperature of the magnesium-containing molten salt is further reduced, and the magnesium-containing molten salt is further promoted to fully melt at the temperature of the first ion exchange, so as to further promote the ion exchange between magnesium ions and tin ions.
[0049] In some embodiments, the float glass raw sheet may further contain magnesium. When the float glass raw sheet contains magnesium, the method for preparing the modified glass raw sheet in the embodiment of the present application may further include the following steps:
[0050] Step S20: immersing the air surface of the float glass raw sheet into a calcium-containing molten salt for a second ion exchange treatment.
[0051] When the float glass sheet contains magnesium, the magnesium ions in the air surface are partially or completely replaced by calcium ions through the second ion exchange treatment, thereby reducing the ion exchange rate of the air surface during the chemical strengthening process, so as to further reduce the difference in ion exchange rate and ion exchange degree between the tin surface and the air surface in the modified glass sheet prepared by the preparation method of the embodiment of the present application during the chemical strengthening process, thereby further reducing the warpage value of the chemically strengthened glass.
[0052] In some embodiments, the temperature of the second ion exchange treatment can be 500-800°C, optionally 500-600°C, 500-750°C, 530-650°C, 550-500°C. In the exemplary embodiment, the temperature of the second ion exchange treatment can be 500°C, 530°C, 550°C, 580°C, 600°C, 630°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, etc., which are typical but non-limiting temperatures, or any temperature between any two numerical ranges. Controlling the temperature of the second ion exchange treatment within this range further promotes the full dissolution of the calcium-containing molten salt, increases the exchange rate of calcium ions and magnesium ions, and promotes the ion exchange between calcium ions and magnesium ions in the air surface of the float glass raw sheet.
[0053] In some embodiments, the time of the second ion exchange treatment can be 0.5 to 4 hours, and can be 0.5 to 3 hours, 0.5 to 2 hours, or 1 to 2 hours. In the exemplary embodiment, the time of the second ion exchange treatment can be 0.5 hours, 0.8 hours, 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, etc., which are typical but non-limiting times, or any time within any two numerical ranges. Controlling the time of the second ion exchange treatment within this range further promotes the full ion exchange between calcium ions and magnesium ions, effectively saves energy consumption, and further improves production efficiency.
[0054] In some embodiments, the calcium-containing molten salt may contain calcium salt, and the calcium salt in the calcium-containing molten salt includes at least one of calcium nitrate and calcium chloride. In a further embodiment, when the calcium-containing molten salt contains calcium nitrate, the mass content of calcium nitrate in the calcium-containing molten salt may be 80% to 100%, optionally 80% to 90%, 90% to 100%. In a demonstration example, when the calcium-containing molten salt contains calcium nitrate, the mass content of calcium nitrate may be 80%, 82%, 85%, 87%, 90%, 92%, 95%, 97%, 100%, etc., which are typical but non-limiting contents, or any content size between any two numerical ranges.
[0055] In some embodiments, the calcium-containing molten salt may also include non-calcium salt components. For example, in the exemplary embodiment, the calcium-containing molten salt may include at least one of lithium nitrate, lithium carbonate, and lithium chloride. In a further embodiment, when the calcium-containing molten salt includes lithium nitrate, the mass content of lithium nitrate may be greater than 0, less than or equal to 20%, and may be 1% to 10%, 5% to 15%, or 10% to 20%. In the exemplary embodiment, when the calcium-containing molten salt includes lithium nitrate, the mass content of lithium nitrate may be 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc., which are typical but non-limiting values, or any value between any two numerical ranges.
[0056] The contents of calcium salts such as calcium nitrate and non-calcium salts such as magnesium nitrate in the calcium-containing molten salt are controlled within this range, so that the calcium-containing molten salt has a higher calcium ion content, and at the same time, the melting temperature of the calcium-containing molten salt is further reduced, and the calcium-containing molten salt is promoted to fully melt at the second ion exchange temperature, so as to further promote the ion exchange between calcium ions and magnesium ions.
[0057] It should be noted that when the modified glass raw sheet preparation method of the present application embodiment includes both the above-mentioned step S10 and step S20, the serial numbers of step S10 and step S20 do not represent the execution order of the two steps. The execution order of step S10 and step S20 is not specifically limited, and step S10 can be executed first, and then step S20; or step S20 can be executed first, and then step S10.
[0058] In some embodiments, the thickness of the float glass sheet used in the modified glass sheet preparation method of the present application embodiment can be 0.1-5mm, and can be 0.1-1mm, 0.1-2mm, 0.1-3mm, 0.3-3mm, 0.3-1.5mm, 0.5-1mm, 0.5-2mm, 0.5-4mm. In the exemplary embodiment, the thickness of the float glass sheet can be 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.2mm, 1.5mm, 1.8mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, etc., which are typical but non-limiting thicknesses, or any thickness between any two values. By controlling the thickness of the float glass sheet within this range, the strength of the chemically strengthened glass produced can be further improved, the warpage value of the chemically strengthened glass can be reduced, and the market demand for increasingly thinner cover glass thickness can be further met.
[0059] In some embodiments, the float glass raw sheet used in the method for preparing the modified glass raw sheet of the present application may include the following components, measured by mass percentage:
[0060]
[0061] In a further embodiment, the float glass raw sheet may include the following components:
[0062]
[0063]
[0064] In some other embodiments, the float glass raw sheet may include the following components:
[0065]
[0066] After the modified glass sheet containing the above components is modified to obtain the modified glass sheet, the warping of the obtained chemically strengthened glass can be further reduced by chemically strengthening the modified glass sheet. In addition, the float glass sheet containing the above components has higher strength after chemical strengthening.
[0067] In a third aspect, the present invention provides a chemically strengthened glass. The chemically strengthened glass in the present invention is prepared by chemically strengthening the modified glass sheet described above, or by chemically strengthening the modified glass sheet prepared by the modified glass sheet preparation method described above.
[0068] Since the magnesium content of the tin surface in the modified glass original sheet is high, and the magnesium element promotes the ion exchange during the chemical strengthening process, the stress depth and stress intensity of the tin surface after the chemical strengthening process are large. In addition, since the difference in the ion exchange rate and the ion exchange degree of the modified glass original sheet during the chemical strengthening process is small, the warpage value of the chemically strengthened glass in the embodiment of the present application is low.
[0069] In some embodiments, the warp value of the chemically strengthened glass of the embodiment of the present application can be 0.18-031 mm, optionally 0.20-0.30 mm, 0.20-0.25 mm. In the exemplary example, the warp value of the chemically strengthened glass of the embodiment of the present application can be 0.18 mm, 0.19 mm, 0.20 mm, 0.21 mm, 0.22 mm, 0.23 mm, 0.24 mm, 0.25 mm, 0.26 mm, 0.27 mm, 0.28 mm, 0.29 mm, 0.30 mm, 0.31 mm and other typical but non-limiting sizes, or any size between any two numerical ranges. Controlling the warp value of the chemically strengthened glass within this range, when the chemically strengthened glass is used in electronic devices, further promotes the close fit of the chemically strengthened glass with other parts and components, and improves the sensitivity of the electronic device. In the exemplary example, the warp value of the chemically strengthened glass of the embodiment of the present application can be the warp value measured for the chemically strengthened glass with a specification of 245 mm × 85 mm × 0.7 mm.
[0070] In a fourth aspect, the present invention provides a method for preparing the chemically strengthened glass mentioned above. The method for preparing the chemically strengthened glass in the present invention comprises the following steps:
[0071] Step G10: chemically strengthen the modified glass sheet to obtain chemically strengthened glass.
[0072] The modified glass sheet in step G10 is the modified glass sheet mentioned above.
[0073] Since the tin surface of the modified glass original sheet has a fast ion exchange rate and a high degree of ion exchange during the chemical strengthening process, the chemically strengthened glass prepared by the chemically strengthened glass preparation method of the present application embodiment has a large stress depth and a large stress intensity. In addition, since the ion exchange rate and the ion exchange degree of the tin surface and the air surface of the modified glass original sheet are slightly different during the chemical strengthening process, the chemically strengthened glass prepared by the chemically strengthened glass preparation method of the present application embodiment has a low warpage value.
[0074] In some embodiments, the chemical strengthening treatment in step G10 may be a one-time strengthening. In an exemplary embodiment, the chemical strengthening treatment may include the following steps:
[0075] Step G21: placing the modified glass sheet in a 100% potassium nitrate solution and performing a third ion exchange treatment to obtain chemically strengthened glass.
[0076] In some embodiments, the temperature of the third ion exchange treatment may be 380-500° C., optionally 380-450° C., 400-500° C., 450-500° C. In an exemplary embodiment, the temperature of the third ion exchange treatment may be 380° C., 390° C., 400° C., 410° C., 420° C., 430° C., 440° C., 450° C., 460° C., 470° C., 480° C., 490° C., 500° C., or any temperature between any two numerical ranges.
[0077] In some embodiments, the third ion exchange treatment time can be 2 to 8 hours, and can be 2 to 5 hours, 3 to 8 hours, 5 to 7 hours, or 5 to 8 hours. In the exemplary embodiment, the third ion exchange treatment time can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, or any time between any two numerical ranges.
[0078] The temperature and time of the third ion exchange treatment are controlled within this range, which further promotes the full progress of ion exchange, promotes the chemical strengthening of the modified glass sheet, and reduces energy consumption in the production process.
[0079] In some embodiments, when the modified glass sheet contains lithium, the chemical strengthening treatment in step G10 may include secondary strengthening. In an exemplary embodiment, when the modified glass sheet contains lithium, the chemical strengthening treatment may include the following steps:
[0080] Step G22: placing the modified glass sheet in a sodium-containing molten salt for a first salt bath treatment to obtain primary strengthened glass;
[0081] Step G23: placing the primary strengthened glass in a potassium-containing molten salt for a second salt bath treatment to obtain chemically strengthened glass.
[0082] Through secondary strengthening treatment, sodium ions are first exchanged with lithium ions in the modified glass sheet, and then potassium ions are exchanged with sodium ions, thereby further improving the stress strength of the chemically strengthened glass.
[0083] In some embodiments, the sodium-containing molten salt used in step G22 may contain sodium salt, and the mass content of the sodium salt may be ≥35%, and the sodium salt may be sodium nitrate. In the exemplary embodiment, the mass content of the sodium salt may be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 85%, 80%, 85%, 90%, 95%, 100%, etc., which are typical but non-limiting values, or any value between any two numerical ranges. The mass content of the sodium salt in the sodium-containing molten salt is controlled within this range, so that the sodium-containing molten salt has sufficient sodium ions, which further promotes the ion exchange during the first salt bath treatment process.
[0084] In some embodiments, the temperature of the first salt bath treatment can be 370-430°C, optionally 370-400°C, 400-430°C; the time of the first salt bath treatment can be 30-300min, optionally 30-100min, 30-200min, 100-300min. In the exemplary embodiment, the temperature of the first salt bath treatment can be 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, etc., but not limiting, or any temperature between any two numerical ranges; the time of the first salt bath treatment can be 30min, 60min, 90min, 120min, 150min, 200min, 250min, 300min, etc., but not limiting, or any time between any two numerical ranges. Controlling the temperature and time of the first salt bath treatment within this range further promotes the full melting of the sodium-containing molten salt and further promotes the full ion exchange during the first salt bath treatment.
[0085] In some embodiments, the potassium-containing molten salt used in step G23 may include potassium salt, and the mass content of potassium salt may be ≥90%, and the potassium salt may be potassium nitrate. In the exemplary embodiment, the mass content of potassium salt in the potassium-containing molten salt may be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc., which are typical but non-limiting values, or any value between any two numerical ranges. Controlling the content of potassium salt in the potassium-containing molten salt within this range further promotes the full ion exchange during the second salt bath treatment, and further improves the stress strength of the obtained chemically strengthened glass.
[0086] In some embodiments, the temperature of the second salt bath treatment can be 370-460°C, optionally 370-450, 370-400, 400-450, 400-460°C; the time of the second salt bath treatment can be 30-300 min, optionally 30-100 min, 30-200 min, 100-300 min. In the exemplary embodiment, the temperature of the second salt bath treatment can be 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, etc., typical but non-limiting temperatures, or any temperature between any two numerical ranges; the time of the second salt bath treatment can be 30 min, 60 min, 90 min, 120 min, 150 min, 200 min, 250 min, 300 min, etc., typical but non-limiting times, or any time between any two numerical ranges. The temperature and time of the second salt bath treatment are controlled within this range, which further promotes the full ion exchange during the second salt bath treatment and further improves the stress intensity and stress depth of the chemically strengthened glass obtained by the method for preparing chemically strengthened glass according to the embodiment of the present application.
[0087] In a fifth aspect, the embodiments of the present application provide a cover glass. The cover glass of the embodiments of the present application includes the chemically strengthened glass mentioned above, or the chemically strengthened glass prepared by the chemically strengthened glass preparation method mentioned above.
[0088] Since the chemically strengthened glass mentioned above has a low warpage value, high stress intensity and great stress depth, the cover glass has low warpage and high strength, and can fit more closely with other components of the electronic device, thereby improving the yield rate of electronic equipment production, reducing production costs, improving the response speed and display quality of the touch screen, and enhancing the user experience.
[0089] In a sixth aspect, an embodiment of the present application provides an electronic device. The electronic device of the embodiment of the present application includes the cover glass described above.
[0090] Due to the low warpage value of the cover glass mentioned above, the touch screen of the electronic device in the embodiment of the present application has a fast response speed, high display quality and good user experience.
[0091] It should be noted that the electronic devices in the embodiments of the present application include but are not limited to mobile phones, computers, tablets, car displays, cameras, game consoles, smart watches, etc.
[0092] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in performance of the modified glass sheet and its preparation method and application in the embodiments of the present application, the above technical solution is illustrated by means of multiple embodiments below.
[0093] 1. Modified glass sheet and preparation method thereof
[0094] Example A1
[0095] This embodiment provides a modified glass sheet. The modified glass sheet of this embodiment is prepared by modifying a float glass sheet, and the float glass sheet includes the following components by mass percentage:
[0096]
[0097] The method for preparing the modified glass sheet of this embodiment comprises the following steps:
[0098] Step S1: providing a float glass original sheet. The size of the float glass original sheet is 245*85*0.7 mm. The amount of tin infiltration on the tin surface of the float glass original sheet before modification is measured using an XRF fluorescence instrument. The results are shown in Table 1.
[0099] Step S2: After preheating the float glass sheet to 600° C., the tin surface of the float glass sheet is placed in a magnesium-containing molten salt for a first ion exchange treatment. The temperature of the first ion exchange treatment is 650° C. and the time is 1 hour. The magnesium-containing molten salt includes 100% magnesium nitrate by mass.
[0100] Step S3: Cool the float glass sheet after the first ion exchange treatment in the above step S2 to room temperature to obtain a modified glass sheet. Clean the surface of the modified glass sheet, use an XRF fluorescence instrument to measure the tin penetration of the tin surface after the first ion exchange treatment; and determine the mass fractions of MgO and Na2O on the air side of the modified glass sheet, calculate their sum, and record it as M1; determine the mass fractions of MgO, Na2O and SnO2 on the tin side, calculate the difference between the total mass fraction of MgO and Na2O and the mass fraction of SnO2, record it as M2, and calculate the ratio of M1 to M2, that is, M1 / M2=([MgO] 空气 +[Na2O] 空气 ) / ([MgO] 锡 +[Na2O] 锡 -[SnO2] 锡 ), and the results are shown in Table 1.
[0101] Embodiment A2 to Embodiment A9
[0102] Embodiments A2 to A9 provide a modified glass sheet respectively. The modified glass sheets of Embodiments A2 to A9 are prepared by modifying the same float glass sheet as that of Embodiment A1. The preparation methods of the modified glass sheets of Embodiments A2 to A9 are basically the same as those of the modified glass sheet of Embodiment A1, except that the pretreatment temperature of the modified glass sheets of Embodiments A2 to A9, the temperature and time of the first ion exchange treatment, and the contents of magnesium nitrate and sodium nitrate in the magnesium-containing molten salt are as shown in Table 1.
[0103] Embodiment A10
[0104] This embodiment provides a modified glass sheet. The modified glass sheet of this embodiment is prepared by modifying a float glass sheet, and the float glass sheet includes the following components by mass percentage:
[0105]
[0106] The method for preparing the modified glass sheet of this embodiment comprises the following steps:
[0107] Step S1: providing a float glass original sheet. The size of the float glass original sheet is 245*85*0.7 mm. The amount of tin infiltration on the tin surface of the float glass original sheet before modification is measured using an XRF fluorescence instrument. The results are shown in Table 1.
[0108] Step S2: After preheating the float glass sheet, the tin surface of the float glass sheet is placed in a magnesium-containing molten salt for a first ion exchange treatment. The preheating temperature of the float glass sheet is 550° C., the first ion exchange treatment temperature is 600° C., the time is 2 hours, and the composition of the magnesium-containing molten salt includes 80% magnesium nitrate and 20% sodium nitrate, as shown in Table 1.
[0109] Step S3: Cool the float glass sheet after the first ion exchange treatment in the above step S2 to room temperature, preheat the glass to 520°C after cleaning, and place the air side in a calcium-containing molten salt for a second ion exchange treatment, cool to room temperature, and obtain a modified glass sheet. The calcium-containing molten salt is 100% calcium nitrate; the temperature of the second ion exchange treatment is 560°C and the time is 2h. Clean the surface of the modified glass sheet, use an XRF fluorescence instrument to measure the tin infiltration amount of the tin surface after the first ion exchange treatment, and the tin infiltration amount is 0.33; and determine the mass content of MgO and Na2O on the air side of the modified glass sheet, calculate their sum, and record it as M1; determine the mass content of MgO, Na2O and SnO2 on the tin side, calculate the difference between the sum of the content of MgO and Na2O and the content of SnO2, record it as M2, and calculate the ratio of M1 to M2, that is, M1 / M2=([MgO] 空气 +[Na2O] 空气 ) / ([MgO] 锡 +[Na2O] 锡 -[SnO2] 锡 ), the results are shown in Table 1. The warpage value is 0.195
[0110] 2. Chemically strengthened glass and its preparation method
[0111] Example B1
[0112] This embodiment provides a chemically strengthened glass, which is obtained by subjecting the modified glass sheet of embodiment A1 to chemical strengthening treatment. The preparation method of the chemically strengthened glass of this embodiment includes the following steps:
[0113] Step G1: providing a modified glass sheet, preheating the modified glass sheet, and then immersing the modified glass sheet in a molten salt of potassium nitrate with a mass fraction of 100% for chemical strengthening treatment to obtain chemically strengthened glass. The temperature of the chemical strengthening treatment is 390° C. and the time is 90 minutes.
[0114] Embodiment B2 to Embodiment B10
[0115] Embodiments B2 to B10 provide a chemically strengthened glass, respectively. Embodiments B2 to B9 chemically strengthened glasses are respectively prepared by chemically strengthening the modified glass sheets of Embodiments A2 to A10, wherein the chemically strengthened glass of Embodiment B2 is prepared by the modified glass sheet of Embodiment A2, the chemically strengthened glass of Embodiment B3 is prepared by the modified glass sheet of Embodiment A3, and so on, the chemically strengthened glass of Embodiment B10 is prepared by the modified glass sheet of Embodiment A10.
[0116] The chemical strengthening treatment methods of the chemically strengthened glass in Examples B2 to B10 are all the same as the chemical strengthening treatment method of the chemically strengthened glass in Example B1.
[0117] Comparative Example B1
[0118] This comparative example provides a chemically strengthened glass, which is made of a float glass sheet that has been chemically strengthened. The float glass sheet used in this comparative example is the same as the float glass sheet used in Example A1, and the chemical strengthening treatment method in this comparative example is the same as the chemical strengthening treatment method in Example B1.
[0119] The tin penetration amount of the tin surface of the modified glass original sheets of Examples A1 to A10 before magnesium ion exchange and the tin penetration amount after magnesium ion exchange are shown in Table 1, wherein the tin penetration amount is measured and detected by an XRF fluorescence instrument.
[0120] The ratio of the total mass fraction of magnesium oxide and sodium oxide on the air side of the modified glass sheets of Examples A1 to A10 after magnesium ion exchange (M1) to the difference between the sum of the mass fractions of magnesium oxide and sodium oxide on the tin side and the mass fraction of tin oxide (M2), that is, M1 / M2=([MgO] 空气 +[Na2O] 空气 ) / ([MgO] 锡 +[Na2O] 锡 -[SnO2] 锡 ) as shown in Table 1.
[0121] The warpage values of the chemically strengthened glasses of Examples B1 to B10 and Comparative Examples B1 and B2 are shown in Table 1.
[0122] Table 1
[0123]
[0124] As shown in Table 1, after the float glass sheets of Examples A1 to A10 were modified to form modified glass sheets, the tin penetration of the tin surface was significantly reduced. Compared with Comparative Example B1, the warpage values of the chemically strengthened glasses of Examples B1 to B10 were significantly reduced.
[0125] Among them, the difference between the chemically strengthened glass of comparative example B1 and the chemically strengthened glasses of examples B1 to B9 is that the chemically strengthened glass of comparative example B1 is made by directly subjecting the float glass original sheet to chemical strengthening treatment, and the tin penetration amount of the tin surface of the float glass original sheet is relatively high; the chemically strengthened glasses of examples B1 to B9 are made by subjecting the float glass original sheet to chemical strengthening treatment after the modification treatment to make the modified glass original sheet, and then subjecting the modified glass original sheet to chemical strengthening treatment, and the tin penetration amount of the tin surface of the modified glass original sheet is relatively low. This shows that the modified glass original sheet and the preparation method thereof provided in the examples of the present application can effectively reduce the warpage of the float glass after chemical strengthening. In examples B7 and B10, after subjecting the float glass original sheet to the first ion exchange treatment to reduce the tin penetration amount of the tin surface, and then subjecting the second ion exchange treatment to reduce the magnesium ion content of the air surface, and subjecting the modified glass original sheet to chemical strengthening treatment, the warpage value of the chemically strengthened glass of example B10 is significantly reduced compared with example B7. This indicates that the warpage value of the chemically strengthened glass can be further reduced by reducing the magnesium ion content on the air side through the second ion exchange treatment.
[0126] In addition, the warpage values of the chemically strengthened glasses of Examples B1 to B9 are all lower than the warpage value of the chemically strengthened glass of Comparative Example B1, which also shows that in the modification process of the float glass original sheet, controlling the first ion exchange treatment temperature within the range of 600 to 680° C. and the content of magnesium nitrate in the magnesium-containing molten salt within the range of 50% to 100% can effectively reduce the warpage of the float glass original sheet after chemical strengthening.
[0127] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A modified glass sheet, characterized in that: The modified glass original sheet comprises a tin surface and an air surface, wherein the magnesium content in the tin surface is higher than the magnesium content in the air surface.
2. The modified glass sheet according to claim 1, characterized in that: The modified glass sheet also contains sodium, and within the depth range of ≤15 μm between the tin surface and the air surface, the contents of sodium, magnesium and tin satisfy ([MgO] 空气 +[Na2O] 空气 ) / ([MgO] 锡 +[Na2O] 锡 -[SnO2] 锡 )=1:(0.95~1.1); and / or When the depth of the tin surface is ≤15 μm, the tin penetration amount of the tin surface is 0.15% to 0.35%; and / or The calcium content of the air side is greater than the calcium content of the tin side; and / or The thickness of the modified glass sheet is 0.1-5 mm.
3. The method for preparing the modified glass sheet according to any one of claims 1 to 2, characterized in that: The steps include: The tin surface of the float glass original sheet is placed in a magnesium-containing molten salt for a first ion exchange treatment to obtain a modified glass original sheet.
4. The preparation method according to claim 3, characterized in that: The temperature of the first ion exchange treatment is 600-680° C.; and / or The first ion exchange treatment lasts for 0.5 to 3 hours; and / or The magnesium-containing molten salt comprises magnesium nitrate with a mass content of 50% to 100% and sodium nitrate with a mass content of 0% to 50%.
5. The preparation method according to any one of claims 3 to 4, characterized in that: The float glass raw sheet contains Mg element, and the preparation method further comprises the following steps: Immersing the air side of the float glass raw sheet in a calcium-containing molten salt for a second ion exchange treatment; Wherein, the second ion exchange treatment satisfies at least one of the following (1) to (4): (1) The temperature of the second ion exchange treatment is 500 to 800° C.; (2) The duration of the second ion exchange treatment is 0.5 to 4 hours; (3) The calcium-containing molten salt comprises calcium nitrate having a mass content of 80% to 100%; (4) The calcium-containing molten salt includes lithium nitrate, and the mass content of the lithium nitrate is greater than 0 and less than or equal to 20%.
6. The preparation method according to any one of claims 3 to 4, characterized in that: The float glass raw sheet has a thickness of 0.1 to 5 mm, and the float glass raw sheet comprises the following components by mass percentage: or 7. A chemically strengthened glass, characterized in that: The chemically strengthened glass is obtained by chemically strengthening a modified glass sheet, wherein the modified glass sheet is the modified glass sheet described in any one of claims 1 to 2 or a modified glass sheet obtained by the method for preparing a modified glass sheet described in any one of claims 3 to 6, wherein the warping value of the chemically strengthened glass is 0.18 to 0.31 mm.
8. The method for preparing chemically strengthened glass according to claim 7, wherein: The steps include: Performing chemical strengthening treatment on the modified glass original sheet to obtain chemically strengthened glass; Wherein, the modified glass original sheet is the modified glass original sheet described in any one of claims 1-2 or the modified glass original sheet prepared by the modified glass original sheet preparation method described in any one of claims 3-6.
9. A cover glass, characterized in that: The invention comprises the chemically strengthened glass according to claim 7 or the chemically strengthened glass produced by the method for producing chemically strengthened glass according to claim 8.
10. An electronic device, characterized in that: Comprising the cover glass as claimed in claim 9.